Proposta de indicadores de uso múltiplo de recursos hídricos aplicado em bacias hidrográficas: estudo de caso - região hidrográfica Tocantins-Araguaia - Cavalcante, Nelson Bernardo Rodrigues (2019)
The strategic and integrated planning of watersheds aims at the multiple use of water with greater efficiency and sustainability, using management tools and instruments for this purpose. Such tools help both in decision making and in informing the population, community and direct users about the current reality of resources and use of watersheds. Thus, this study proposes the development of indicators, whose main objective is to characterize the situation of watersheds in terms of the capacity to meet the demands of water resource use. The methodology proposes a system that uses available data, starting with the systemization of data, definition of preferences and parameters, previously determining the ways of obtaining and following for the treatment and aggregation, resulting in a group of indicators. The Tocantins-Araguaia hydrographic region (RHTA), was defined as a case study because it is one of great water importance for the country and presents great potential for growth in the use of water resources. The result obtained from the analysis of the indicators generated by the study showed the great water potential and importance of the Tocantins River basin, as well as the need for integrated planning between the uses for some watersheds, which are at a critical level of scarcity.